"Big" Treaties, Small Effects: The RTAA Agreements. (6th March 2018) - Gowa, Joanne; Hicks, Raymond
Abstract : It seems obvious that agreements to cut tariffs will raise trade between their signatories. But recent studies show that some agreements widely considered to be landmarks in economic history had either a remarkably small impact on trade or none at all. Among those agreements are the Cobden-Chevalier Treaties and the long series of tariff accords concluded under the auspices of the GATT/WTO. Both sets of agreements cut import duties on many goods that applied to all trading partners entitled to most-favored-nation treatment, but neither increased aggregate trade between their members. This article examines the agreements concluded by the United States under the 1934 Reciprocal Trade Agreements Act (RTAA). The authors use an original data set that records changes in tariffs and US imports at the product-line level for each of the twenty-seven bilateral agreements. No comparable data exist either for the nineteenth-century trade network or for the postwar trade regime. The results show that the RTAA treaties failed to raise aggregate US imports from its treaty partners. They also show that these agreements did lead to a large and significant rise in US imports of specific products from specific countries. Because the same bargaining protocol that produced the RTAA agreements also governed the European treaty network and the GATT/WTO, the argument advanced in this article can also help to explain why neither treaty exerted a significant impact on aggregate trade between their signatories.